1986
DOI: 10.1149/1.2108405
|View full text |Cite
|
Sign up to set email alerts
|

Metalization of AlN Ceramics by Electroless Ni‐P Plating

Abstract: ELECTROLESS PLATED AND THIN FILMS 2345 field distribution. Br " 5/Hc for the Co-Ni-P is 14.3, compared to 23.3 for the Co-P. The decrease in demagnetization parameter resulted in an increase in DT0 from 18.5 KFCI for Co-P to 22 KFCI for Co-Ni-P (Fig. 8) when tested with a thin film head with gap length 30 win., 15 turns, at a fly height of 8 win. Therefore, when appropriately deposited, Co-Ni-P films can support higher recording density compared to Co-P films. ABSTRACTHighly thermally conductive aluminum nitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…The most widely applied methods are the deposition of a Ni or Ni alloy layer on the surface of the thermoelectric element [18][19][20][21][22]. That is, an Ni or Ni alloy acting as a diffusion barrier is incorporated by electroplating, electroless plating, physical vapor deposition (PVD), or the thermal spraying process.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely applied methods are the deposition of a Ni or Ni alloy layer on the surface of the thermoelectric element [18][19][20][21][22]. That is, an Ni or Ni alloy acting as a diffusion barrier is incorporated by electroplating, electroless plating, physical vapor deposition (PVD), or the thermal spraying process.…”
Section: Introductionmentioning
confidence: 99%
“…The process of joining AlN to metals and ceramics has been investigated by many researchers. For combination with metals, many reports have been published on directly joining AlN to copper, joining it to metals using active fillers, and the electroless plating of copper/nickel films on AlN substrates . Joining AlN to massive ceramic materials has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Good wetting for Ni alloyed with Ti, Zr, and Hf was reported [5]. A wide variety of processes for metallization of AlN have been proposed, such as thick film metallization [6]- [11]; soldering [12] and brazing [13]; direct bonding [14]; cofiring with high melting point metals [15]; electroless plating [16]- [18]; and hot pressure bonding [19]. Among these metallization methods, the electroless Ni (EN) plating method appears to be the most appropriate one because the thermal expansion coefficient [20(a)] lower than that of Cu and also closer to that of AlN ceramic.…”
Section: Introductionmentioning
confidence: 99%
“…Although electroless Ni (EN) plating is a promising method for metallizing the oxide ceramics, such as few of them concentrate on AlN [16], [17]. It has been reported that the adhesion strength of EN film is related to the surface morphology of AlN substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation